Hospitality and the enlightenment (encountering China) - Greve, Anni, author. aut Link Link Link
1 online resource.
Keywords: "This book draws out the relationship between the shift in hospitality to the foreigner and the European Enlightenment during the so-called long eighteenth century - a relationship pertinent to today's landscape. It focuses on the significance of 'free cities', which have at crucial times functioned as a practice room for extended communication, the art of arguing, friendship and conversation. Greve begins by unfolding the philosophy of hospitality by reading both Immanuel Kant and Jacques Derrida, before turning to China's global role. The book discusses Chinese hospitality with the Canton system of 1757 and the hospitality offered to the Sephardic diaspora, related to: the first experience of global interconnectedness and the birth of the global silver market; diaspora corridors as spaces of hospitality: the case of the 'free' port city; and, their role as notaries and translators in long-distance credit relations. It then turns to Copenhagen, delving into the city's prominence in the European trade with China and what this signified for the Enlightenment. Finally, the book returns to the China of today. What has the opening of China in the 'new era' after Mao Zedong implied? And how to understand an urge for a new enlightenment, first in the late 1980s in Beijing and next in the 2020s in the 'free' port city of Hong Kong? The volume is a valuable resource for students and scholars interested in the Enlightenment, diaspora studies, urban studies, philosophy and China in global history"-- Provided by publisher.